Transformation of the self in the thought of Friedrich Schleiermacher - Mariña, Jacqueline (Oxford University Press, 2008)
The philosopher's stone -- The principle of individuation -- Personal identity -- The world is the mirror of the self -- The highest good -- Individual and community -- Transformation of the self through Christ -- Outpourings of the inner fire : experiential expressivism and religious pluralism